A review of mitochondrial SNP determination using allele-specific PCR in forensic identification - Shalini Parthipan,; Mohitha Sandrasagran,; Seri Mirianti Ishar, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Allele-specific polymerase chain reaction (AS-PCR) is a rapid and cost-effective single nucleotide polymorphism (SNP) genotyping method compared to multiplex or real-time PCR. The SNPs occurring in mitochondrial DNA (mtSNPs) is the most abundant polymorphism in humans and can be used in human identification involving mass fatality incidents. Nevertheless, the application of AS-PCR has yet to be widely applicable in forensic investigations because this method requires further development due to its limitations. This review aims to relate the applications of AS-PCR, the combination of AS-PCR with other PCR techniques and improvements imposed on this technique in past studies. A narrative literature review was carried out over 70 studies related to the mtDNA, SNP, AS-PCR, and forensic DNA. The findings suggested that AS-PCR with new adaptations in technology such as incorporating additional mismatch, choosing allele-specific primer with either common forward or reverse, gel free real-time AS-PCR analysis, and usage of fluorescence probes can improve the specificity of SNP genotyping in forensic applications. This review concludes that AS-PCR and its combination with other improvised techniques can be applied in human identification to successfully analyze degraded or low quantity samples. Nevertheless, development of more SNP loci is required to implement AS-PCR in human identification to match the current gold standard STR typing method.